Knowledge of children’s Mothers with thalassemia about thalassemia disease - البيرق كوكب (Latakia University Journal -Medical Sciences Series, 2023)
Thalassemia is one of the most common physical disorders in the world. Affected children are exposed to complications and health risks that may be life-threatening. Parents’ knowledge of the nature of this disease constitutes a fundamental pillar in avoiding complications and improving the quality of life for the child. Therefore, the current descriptive study aimed to identify the Knowledge of a convenient sample of 50 mothers who have a child with thalassemia about thalassemia disease, in the Department of Hematology at the Maternity and Children Hospital in Lattakia City, and data were collected using a questionnaire developed by the researcher. The study concluded that the Knowledge level of 60% of the mothers was moderate about thalassemia, and they all knew that thalassemia patients could be identified through blood analysis, and that thalassemia is a blood disease. However, they did not know that medication is the only solution for treating thalassemia. The study recommended the need to put pictures of illustrative posters about thalassemia in the places of treatment, conduct continuous awareness sessions for parents about the complications of the disease and ways to adapt and manage it, and conduct research on the factors affecting parents’ information about thalassemia